The Influence Of Public Perception, Social Media, And Content Type On Bimba Baca Brand Awareness - Nopiah, Neneng; Hidayatulloh, Furqon Syarief; Purwono, Joko (Indonesian Journal of Multidisciplinary Science, 2025)
West Java Province, with the largest population in Indonesia, and Sukabumi Regency, which boasts the widest area and a substantial population, also exhibit a significant proportion of young children. The 2025-2045 National Long-Term Development Plan highlighted the pivotal role of quality education as a cornerstone of national development. The Indonesian education system, as stipulated in Law No. 20 of 2003, encompasses formal, non-formal, and informal pathways. Early childhood education is a key focus, given the substantial presence of this demographic. Child reading and learning interest guidance, known as bimba, represents non-formal education for young children. Bimba Baca Sukabumi located in Sukabumi Regency, employs diverse learning methods designed to provide targeted stimulation for early childhood development and support the Indonesia Emas 2045. Enhancing Bimba Baca Sukabumi's brand awareness is crucial for contributing to the achievement of Indonesia Emas 2045. Social media, digital content, and perception management are effective tools for disseminating information and building brand awareness. This research was conducted at Bimba Baca Sukabumi. The study utilized purposive sampling, selecting respondents based on criteria representative of the variables. Kotler's Marketing Theory and Kelley's Attribution Theory served as the theoretical foundation for variable determination. The independent variables examined included public perception, social media usage, and content type, while brand awareness was the dependent variable. The research employed the SEM-PLS analysis method to analyze the influence of public perception, social media, and digital content on public brand awareness of Bimba Baca Sukabumi.